Single Founder Mutation (W380G) in Type II Protein C Deficiency in Finland - Levo, Antti; Kuismanen, Kristiina; Holopainen, Päivi; Vahtera, Elina; Rasi, Vesa; Krusius, Tom; Partanen, Jukka (Thrombosis and Haemostasis, 2000)
The present study investigated the genetic basis for type II protein C deficiency in Finland, where this form has an unusually high incidence. We demonstrated that, first, a single novel mutation W380G in the protein C gene (PROC) explained 25/26 index patients, estimated to represent two thirds of all families with type II deficiency in Finland. Second, extended chromosomal conservation, i. e. a specific haplotype, around the W380G mutation was indicated in unrelated patients. Third, a local geographical origin for the W380G mutation was suggested by genealogical data. These results are in contrast to the heterogeneity in type II protein C deficiency elsewhere, but closely parallel disorders of the Finnish disease heritage. The high frequency of the type II disease can be explained by founder effect and subsequent enrichment of a single mutation in Finland. The present study also provided a simple means for genetic diagnosis of this disease and the genetic test can be included in the routine screenings in this population.
Keywords: Protein C; thrombosis; genetic disorders; Finnish population; mutation; PROC gene